HUBUNGAN SANITASI LINGKUNGAN RUMAH DENGAN KEJADIAN DIARE PADA BALITA DI WILAYAH KERJA PUSKESMAS KARANGANYAR KABUPATEN PEKALONGAN - Menik Samiyati; Suhartono Suhartono; Dharminto Dharminto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Diarrhea is a disease with high cause of death of toddlers, so that this disease is considered a health problem that cannot be dealt of developing country. Karanganyar’s Health Center is a working area with the discovery of high diarrheal diseases in Pekalongan Regency in 2017 with 333 toddler cases. The sanitation condition of the home environment is a factor causing diarrhea. The purpose of the study was to determine the relationship of home environmental sanitation with the case of diarrhea in toddlers in the working area of the Karanganyar’s health center in Pekalongan. The study used a cross sectional approach with a sample of 64 respondents. The results showed that 54.7% of toddlers who suffered from diarrhea with clean water facilities did not meet the requirements 71% unsafe drinking water sources 65% of the toilet conditions did not meet the requirements 72.5% of sewerage did not meet the requirements 55.8% of floor’s types were not 100% waterproof. The results of the bivariate analysis showed that the variable of clean water facilities p=0.022, the condition of drinking water facilities p=0.010, the toilet conditions p=0.010, the sewerage p=1.000, and the type of floor p=0,497. It was concluded that there was a significant relationship between the condition of clean water facilities and the condition of the toilets in the working area of the Karanganyar’s Health Center in Pekalongan Regency.